Accounting Conservatism and Debt Contracts: Efficient Liquidation and Covenant Renegotiation - LI, Jing (Contemporary Accounting Research, 2013)
This paper develops a theoretical model to understand the role of accounting con- servatism in debt contracts, incorporating the possible renegotiation of debt contracts with accounting-based covenants. I find that the demand for accounting conservatism depends on whether renegotiation occurs and if so, at what cost. When the covenant is not renegotiable or when renegotiation cost is sufficiently high, more conservative accounting actually reduces the efficiency of debt contracts. When renegotiation cost is moderate, more conservative accounting may increase the entrepreneur's welfare under certain conditions, especially for firms with less promising investment opportunities and for firms with higher liquidation values. Both are characteristics of "traditional industries" characterized by low growth and high level of tangible assets in place. When renegotiation is costless, the degree of accounting conservatism becomes irrelevant and the first best liquidation is always achieved. These results call for more cross-sectional examinations on the role of accounting conservatism in debt contracts in empirical studies.